Specialty Coffee in the United Arab Emirates: Challenges and Opportunities - Kurniawan Arif Maspul (CV. Ulil Albab Corp, 2022)
The UAE has potential and opportunities from all stakeholders to revitalise the country as a hub of specialty coffee in the Middle East. Nevertheless, with the agitating demand for coffee, where only 60% is met by global coffee supply from smallholders, besides five countries that limit the production of 72% of coffee in the world. In addition to the challenge of the world's demand for 25% of coffee in 2030, will specialty coffee be sustainable for future generations (WCR, 2021)? All stakeholders from leaders need challenges to embrace and cooperate; restore all chains from farmers' needs as the core of coffee itself. The UAE will become sustainable in every coffee value chain if UAE can overcome this challenge as early as possible. It is hoped that all opportunities will be able to create an absolute three bottom legs of sustainability in the coffee farm, which will support future needs.